Road Infrastructure and Local Economic Activity: Insight from Mobility Data - Kustanto, Raditya Yudhan; Mahi, Benedictus Raksaka (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2025)
Research Originality: This research measures local economic activity through a mobility approach, using Google Mobility Report (GMR) data across all provinces in Indonesia. Measuring economic activity using conventional macro indicators, such as GDP, has limitations due to lengthy collection processes.Research Objectives: This study aims to determine the impact of road infrastructure on local economic activity using data from the GMR in categories such as Retail and recreation, Grocery and pharmacy, Parks, and Workplaces.Research Methods: This study uses panel data on the GMR, Ministry of Public Works and Public Housing, Ministry of Finance, and Central Bureau of Statistics from 2019–2022, which is analyzed using fixed-effect methods.Empirical Results: The results show a positive effect of road infrastructure on Retail and recreation and Grocery and pharmacy but a negative impact on Workplaces, likely due to the shift to remote work during COVID-19.Implications: These findings suggest that the government should prioritize road construction in areas that enhance economic activity. However, road construction in the Workplaces area still needs to be considered in line with the recovery of activities after the pandemic ends.JEL Classification: H54, R11, R42How to Cite:Kustanto, R.Y., & Mahi, B.R. (2025). Road Infrastructure and Local Economic Activity: Insight from Mobility Data. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 17-36. htttps://doi.org/10.15408/sjie.v14i1.42955.